Adapting knowledge workers with knowledge Management System and its use in organization / Alwi Mohd Yunus ... [et al.] - Mohd Yunus, Alwi; Nik Ariffin, Nik Azliza; Mohd Bakri, Asyraf; Ismail, Muhammad Afiq Ismail; Abdul Malik, Nur Hamezah (Universiti Teknologi MARA, Selangor, 2020)
A Knowledge Management System (KMS) is very important for organization to applying and using knowledge management practices. These include data-driven object around business productivity, a competitive business model, business intelligence analysis, and more. A KMS is made up of different software modules served by a central user interface. Some of these features can allow for data mining on customer input and histories, along with the provision or sharing of electronic documents. The purpose of the case study is to identify the adaptation of knowledge worker when using the KMS in organizations. Studies are made on critical aspects of Knowledge Management System research, case study, general review, and conceptual papers that were written by researchers in the topic of interest